Influence of dietary supplementation with Bacillus licheniformis and Saccharomyces cerevisiae as alternatives to monensin on growth performance, antioxidant, immunity, ruminal fermentation and microbial diversity of fattening lambs. Issue 1 (December 2018) - Jia, Peng; Cui, Kai; Ma, Tao; Wan, Fan; Wang, Wenyi; Yang, Dong; Wang, Yunfei; Guo, Baolin; Zhao, Lifang; Diao, Qiyu
Abstract Alternatives to antibiotics for improving productivity and maintaining the health of livestock health are urgently needed. The scope of this research was conducted to investigate the effects of two alternatives (Bacillus licheniformis andSaccharomyces cerevisiae ) to monensin on growth performance, antioxidant capacity, immunity, ruminal fermentation and microbial diversity of fattening lambs. One hundred and sixty Dorper × Thin-tailed Han sheep (32 ± 3.45 kg BW) were randomly assigned into 5 treatments of n = 32 lambs/group. Lambs in the control group were fed a basal diet (NC) while the other four treatments were fed basal diets supplemented with monensin (PC), Bacillus licheniformis (BL), Saccharomyces cerevisiae (SC), and the combination ofBacillus licheniformis andSaccharomyces cerevisiae with protease (BS), respectively. The experiment lasted for 66 d. Feed intake was recorded every 2 d and lambs were weighed every 20 d. Ten lambs from each group were slaughtered at the end of the trial, and samples of serum and rumen fluid were collected. The results indicated that the dietary regimen did not affect the dry matter intake (DMI). The average daily gain (ADG) of BS treatment was significantly higher than NC group (P  < 0.05). Compared with the NC treatment, the other four supplementation treatments increased the concentration of growth hormone (GH), insulin-like growth factor I (IGF-I) and insulin (INS) (P  < 0.05). The malondialdehyde (MDA) and total antioxidant capacity (TAOC) showed no significant difference among the 5 treatments while the activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) of BS group was significantly increased (P  < 0.05). The supplementation regimen decreased the concentration of ammonia Nitrogen (NH3 -N) and increased the content of microbial crude proteins (MCP) (P  < 0.05). The supplementation of antibiotics and probiotics reduced the concentrations of acetate and increased the concentrations of propionate (P  < 0.05). The supplementation treatments increased the relative abundance ofLentisphaerae, Fibrobacteres andTenericutes at the phylum level, whereas at the genus level, they increased the relative abundance ofFibrobacter (P  < 0.05). Overall, this study confirmed the facilitating effect ofB .licheniformis, S .cerevisiae and their compounds on growth performance, improve the antioxidant capacity and immune function, and beneficially manipulate ruminal fermentation and microbial diversity of fatting lambs.